Factors Influencing Systematic Thinking Mechanisms in Islamic Education: System Model, Development, and Control - Halim, Abdul; Ali, Hapzi; Imron Rosadi, Kemas (Green Publisher, 2024)
Factors that influence Systemic Thinking in Islamic Education, System Model, Development and Control are scientific articles in literature studies within the scope of the field of science. The purpose of this article is to build a hypothesis of the influence between variables that will be used in further research. Research objects in online libraries, Google Scholar, Mendeley and other academic online media. The research method with the research library comes from e-books and open access e-journals. Qualitative descriptive analysis. Results this article: 1) Factors that affect the mechanism of Systemic Thinking 2) Factors that affect the System Model 3) Factors that affect Development and 4) factors that affect control.